The eighth TNM classification for malignant pleural mesothelioma - Berzenji, Lawek; Van Schil, Paul E.; Carp, Laurens (Translational Lung Cancer Research; Vol 7, No 5 (October 18, 2018): Translational Lung Cancer Research (Malignant Pleural and Peritoneal Mesothelioma), 2018)
In 2016, the International Association for the Study of Lung Cancer (IASLC) published a number of revisions of the seventh edition of the tumor, node and metastasis (TNM) classification for malignant pleural mesothelioma (MPM). The purpose was to establish a set of recommendations for the eighth edition of the TNM staging system. A large number of patients were included in the IASLC database and subsequently analysed to determine new definitions for the components of the TNM classification. A number of important changes were introduced for the T component. Survival analysis of the different T categories showed no significant difference in categories T1a and T1b. This has resulted in a collapse of categories T1a and T1b into one category T1. In addition, tumor thickness was also significantly associated with overall survival. The descriptors for the N components have been redefined as well for the eighth TNM classification. A major revision is the removal of category N3 in the N component. Both intrapleural and extrapleural (N1 and N2 in the seventh edition) are now combined into a single category N1. Lymph nodes that were previously categorized as N3 are now considered N2. For the M component, no redefinition has been published. However, a recommendation has been made to only consider M1 involvement as stage IV disease. This is in contrast to the seventh edition in which T4 and N3 disease were considered stage IV as well. In conclusion, a number of important revisions for the eighth TNM classification of MPM have been published as a result of this IASLC project. This type of large-scale and international joint efforts are key in establishing effective staging systems. Research into using tumor thickness as a prognostic instrument will be an important part of any future editions of the TNM classification.